1992
DOI: 10.1002/chp.4750120308
|View full text |Cite
|
Sign up to set email alerts
|

Targeting continuing medical education on decision makers: Who decides to transfuse blood?

Abstract: A communication analysis study was designed and conducted to analyze patterns of communication between operating room (OR) personnel about transfusion practice during open heart surgery. The purpose was to identib the transfusion medicine decision maker in order to target OR personnel for subsequent continuing medical education (CME). Targeting the decision makers for CME intervention would ( I ) improve transfusion practice for quality assurance and ( 2 ) increase the efficiency ofproviding CME. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…The results of this analysis indicated that transfusion medicine education programmes should be designed to reduce homologous blood exposure. 17 Ironic compared to the usual concept that good knowledge translates to good practice, in the present study, practices were found to be better than attitude and knowledge. This was probably because the induction and educational module consisted more of pictorial depictions and video demonstrations, which influence practices better.…”
Section: Discussioncontrasting
confidence: 64%
“…The results of this analysis indicated that transfusion medicine education programmes should be designed to reduce homologous blood exposure. 17 Ironic compared to the usual concept that good knowledge translates to good practice, in the present study, practices were found to be better than attitude and knowledge. This was probably because the induction and educational module consisted more of pictorial depictions and video demonstrations, which influence practices better.…”
Section: Discussioncontrasting
confidence: 64%
“…One inherent difficulty in assessing the relative risks and benefits in the decision to transfuse is that the benefit of blood for the individual patient can be appreciated immediately, whereas the complications of blood are often seen at a time remote to the transfusion event, many years later (Welch et al, 1992). Within the traditional concept that blood is a useful therapeutic intervention, it is understandable that efforts to curtail unnecessary transfusions have been largely unsuccessful; despite guidelines (NIH, 1988) and utilization review recommendations (JCAHO, 1988;Silberstein et al, 1989) for blood transfusions, evidence indicates continued inappropriate use (Friedman, 1978;Friedman et al, 1980;Coffin et al, 1989;Goodnough et al, 1991). The concept of blood transfusion as an outcome to be avoided if possible (American College of Physicians 1992; Welch e l al., 1992) has arisen from issues of blood risks over the last 10 years; the legislation of blood shield laws by nearly every state that defines blood as a service, rather than as a product whose safety cannot be warranted is based on the concept that blood administration has inherent risks (Zuck, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In coronary artery bypass graft surgery, 79% of blood units were transfused on the day of surgery (Goodnough et al, 1994), so that utilization review criteria and physician education programmes that focus on the nadir haematocrit as a clinical indicator (NIH, 1988;Silberstein et af., 1989) may have limited effectiveness in this setting. Secondly, the discharge haernatocrit has been used as a parameter to determine blood lost during hospitalization (Goodnough et al, 1991), and could therefore serve as a clinical indicator in which utilization review for transfusion appropriateness is defined by each patient's red cell losses as a percentage of their initial circulating red cell volume. Finally, transfusion decisions prior to discharge are made on the basis of this recorded haematocrit, in which the blood volume status of the patient is stable and the degree of anaemia is accurately reflected by the level of haematocrit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations